Evaluation of forage legumes in the semi-arid region of eastern Kenya. 2: persistence and dry matter production of selected forage legumes - W.M. Beattie (Tropical and Subtropical Agroecosystems, 2004)
Twenty forage legumes consisting of 5 short livedannuals (SLA), 5 long lived annuals (LLA) and 10perennials were evaluated for persistence andproductivity at 4 sites; Katumani, Kiboko, Mua Hillsand Ithookwe within the semi-arid tropics of easternKenya. The legumes were sown in plots of 4 m x 4 mand after emergence, they were monitored forpopulation and repeatedly harvested for accumulateddry matter production for a period of 3 rainy seasonscomprising about one and half years. There weresignificant (P<0.05) difference in numbers of plants anddry matter (DM) production between legumes withinthe same site. Major LLA, Lablab purpureus cv. Rongaiand Dolichos lablab K1002, and SLA, Vignaunguiculata cvv. Red Caloona and M66 had highestplant numbers at establishment in all the sites. While theLLA showed a reduced plant numbers towards the endof experiment, the SLA failed to persist beyond thesecond rainy season. For the perennials, although plantnumbers declined after establishment, they maintained areasonable plant population at the end of theexperimental period. There was poor survival of alllegumes at Kiboko compared to the other sites andStylosanthes scabra cv. Fitzroy and Rhynchosiamalacophylla K18176 showed the best survival abilityacross all the sites. Vigna unguiculata M66 and Lablabpurpureus cv. Rongai outyielded all other the legumesin harvest 1. While M66 recorded no yield insubsequent harvest, yield for Rongai increasedsubstantially during harvest 2 at Mua Hills, remainedfairly stable at Katumani but declined drastically atKiboko and Ithookwe. In harvests 3 and 4 yielddeclined at all the sites for this legume The initialgrowth of perennials such Stylosanthes scabra cv.Fitzroy, Neonotonia wightii K75.2366, Desmodiumintortum cv. Greenleaf and Rhynchosia malacophyllaK18176 were slow and were more productive from thesecond harvest and maintained a reasonable dry matteryield even in competition with weeds. Generally DMproduction was considerably reduced at the drier site ofKiboko and majority of the legumes disappeared aftersecond harvest. By harvest 4, only 4 legumes, allperennials remained productive but yield were less than300 kg/ha. Plant population and DM production wasgreatly influenced by rainfall with the wetter site of MuaHills having the more plants surviving and highest DMproduction. These legumes have potential for use in thevarious farming of the semi-arid of eastern Kenya andthere is need to investigate further how they can beintegrated.